Characteristics of Phosphorus Adsorption and Release in Different Types of Sediments (International Journal of Scientific Research and Management (IJSRM), 2020)
Taking different types of sediments as the research object, this research studied the adsorption and release characteristics of phosphorus under different conditions of different temperatures, coexisting heavy metal ion system, organic matter content and sediment particle size. Through used correlation analysis and principal component analysis, it discussed the influence of various factors on the adsorption and release of phosphorus in sediments. The results show that the adsorption of phosphorus by five different types of sediments from different sources reached saturation equilibrium in about 10 hours, and the increasing rates of 0 ℃, 15 ℃ and 30 ℃ are 17.5% 23.7% and 18.2% 38.3%, respectively. The addition of coexisting heavy metal ion solution accelerated the adsorption of phosphorus in the sediment and reduced the total amount of phosphorus adsorption, that is, heavy metal ions inhibited the adsorption of phosphorus in the sediment; the presence of organic matter in the sediment would reduce its adsorption of phosphorus , Taihu farm and wetland sampling points have the largest sediment organic matter content. Compared with the other three points, the adsorption of phosphorus of these two points accounted for 20.6% and 22.1%; the adsorption and release of phosphorus by sediment increased with the decrease of particle size. The maximum release rate was 5.216mg/kg-1·h-1. The result of principal component analysis shows that the order of influence on the adsorption and release of phosphorus by sediments is temperature> disturbance> organic matter content> heavy metal ion influence> particle size of sediments.